Sekolah Alam Care Education For All Islamic School Kecamatan Tapung Kampar Riau - Nurshafira, Wan; Sidiq, Siti Sofro (Jurnal Ilmiah Wahana Pendidikan, 2025)
Nature Schools is one of the non- formality with nature-based in its implementation. The emergence of Nature Schools is one of the reactions to the current ugly education system. This study aims to find out the liberating education in nature schools as well as the rational choice of parents in choosing CEFA Islamic School for their children. Research was also conducted to find out the responses of parents regarding the CEFA Nature School. This study uses a descriptive qualitative method by using observation, interview and documentation techniques as data collection tools. Based on the results of the study, it was found that there are liberating educational practices in CEFA Nature Schools with freedom in learning and two-way communication between teachers and students. The rational choice of parents in choosing CEFA Nature School is based on several factors, namely because of the large portion of religious education, word-of-mouth information, trust, affordable costs, close enough mileage, does not make children depressed and stressed with education, and can be a way to find potential, as well as children's interests and talents. The response of parents to CEFA Nature School is very positive by seeing the development in the child's personality such as becoming more diligent in worship, independent, willing to help with homework, more confident, and having social skills.